Economically important sea cucumber processing techniques in South Sulawesi, Indonesia. (November 2019) - Aprianto, R; Amir, N; Kasmiati,; Matusalach,; Fahrul,; Syahrul,; Tresnati, J; Tuwo, A; Nakajima, M
Abstract: Sea cucumbers are fisheries commodities that have important economic value. Indonesia is the largest producer of sea cucumbers in the world, and South Sulawesi Province is the largest producer of sea cucumbers in Indonesia. Although the export volume of Indonesian dried sea cucumbers or trepang is large, the export value is not high due to the low quality of trepang. This study aims to examine the techniques or method of sea cucumber processing in two locations in South Sulawesi where sea cucumbers are processed to produce trepang. The study was conducted by observing the processing stages used in the Sembilan Islands Sub-District, Sinjai Regency and Labbakkang Sub-District, Pangkep Regency. The study found that, in general, the basic stages in trepang processing were removal of the viscera, salting, boiling and drying. The most prominent difference in the processing of trepang in the two research areas was the lack of a fumigation process. In other countries where the quality of trepang is better; the process of fumigation is an important stage to increase the durability and aroma of trepang.